The returns to seniority in France (and why are they lower than in the United States?) - Magali Beffy; Moshe Buchinsky; Denis Fougère; Thierry Kamionka; Francis Kramarz (Institute for the Study of Labor (IZA), 2006)
We estimate a model of the joint participation and mobility along with the individuals' wage formation in France. Our model makes it possible to distinguish between unobserved person heterogeneity and state-dependence. We estimate the model using state of the art Bayesian methods employing a long panel (1976-1995) for France. Our results clearly show that returns to seniority are small, and for some education groups are close to zero. The specification here is the same as that used in Buchinsky, Fougre, Kramarz and Tchernis (2002), where the returns to seniority were found to be quite large. This result also holds when using the method employed by Altonji and Williams (1992) for both countries. It turns out that differences between the two countries relate to firm-to-firm mobility. Using a model of Burdett and Coles (2003), we explain the rationale for this phenomenon. Specifically, in a low-mobility country such as France, there is little gain in compensating workers for long tenures because they tend to stay in the firm for most, if not all, of their career. This is true even in cases where individuals clearly possess substantial amount of firm-specific human capital. In contrast, for a high-mobility country such as the United States, high returns to seniority have a clear incentive effect, and firms are induced to pay the premium associated with firm-specific human capital to avoid losing their most productive workers.
Keywords: J24; J31; J63; 330; participation; wage; job mobility; returns to seniority; returns to experience; individual effects; Ältere Arbeitskräfte; Senioritätsentlohnung; Betriebszugehörigkeit; Lernprozess; Arbeitsmobilität; Vergleich; Frankreich; USA